ANALISIS DAMPAK BIAYA MODAL TERHADAP KEPUTUSAN INVESTASI PERUSAHAAN - M. Fadly Syahputra; Ansari, Ansari (Journal of Innovation Research and Knowledge, 2024)
This study aims to analyze the impact of the cost of capital on corporate investment decisions. In an increasingly complex economic context, companies are required to consider the cost of capital in every investment decision to ensure the feasibility and sustainability of projects. The approach used in this research is qualitative with an exploratory case study method. Data were collected through in-depth interviews with financial managers, CFOs, and company leaders directly involved in investment decision-making, as well as observations and document analysis. The findings of the study indicate that the cost of capital, which includes the cost of debt and equity, has a significant influence in guiding investment decisions. Companies with a more diverse capital structure tend to have greater flexibility in managing their cost of capital, while companies with a higher proportion of debt are more cautious in making investment decisions. The findings also reveal that companies that are more innovative in managing their cost of capital succeed in finding lower-cost funding sources and diversifying their investment portfolios. This study suggests the importance of improving financial literacy for small and medium-sized enterprises and optimizing capital structure to reduce overall cost of capital. Additionally government policies that support access to more affordable financing should be considered.